공급업체 만족도 설문 분석에 근거한 중요 협업 비즈니스 요인 규명과 개선 우선순위 결정 - 임지연(Lim, Ji-Youn); 이장희(Lee, Jang-Hee) (대한경영학회지, 2012)
기업 간 협업 비즈니스 프로세스를 관리하는 전통적인 접근 방식은 주로 협업 비즈니스 프로세스 관리 시스템의 개발 또는 개념적 측면에서 공급업체에 대한 평가 방식에 중점을 두고 있다. 이러한 기존의 접근 방식은 프로세스 결과 향상에 초점을 맞춰 공급업체 관리 및 협업 비즈니스 프로세스 수행을 위한 적절한 전략을 제시하는 반면, 대부분 실무 수준에서의 협업 비즈니스 프로세스의 개선을 위한 세부 절차를 제시하지 못하고 있다. 본 연구는 공급업체를 대상으로 수행하는 설문 조사 데이터를 분석하여 실무 수준에서의 협업 프로세스 상 중요하게 관리되어야 하는 비즈니스 프로세스를 효율적으로 발견하고 각각의 업체별로 어떤 협업 비즈니스 프로세스를 우선적으로 개선할 것인지 구체적이고 실제적인 분석 프레임 워크를 제안한다. 본 연구에서 제시하는 분석 프레임 워크에서는 공급업체를 대상으로 수행하는 설문문항을 세부적인 협업 비즈니스 프로세스를 반영하도록 설계한다. 공급업체 직원 만족도를 바탕으로 작성된 설문 데이터는 K-means 클러스터링 알고리즘, 의사결정트리 분석 및 AHP (Analytic Hierarch Process) 분석 도구를 활용하여 분석하여 현업에서 개선이 필요한 것으로 파악되는 공급업체와 관련된 중요한 협업 프로세스와 관련된 관리 요인 도출하고 시급히 개선되어야 하는 프로세스 관련 관리 요인들을 제시한다. 제안한 분석 프레임 워크는 국내 대형 여행사에서 협업을 수행하고 있는 업체와의 협업 사례에 적용함으로써 실무 적용의 타당성을 분석하였다. 분석 결과, 국내 대형 여행사의 공급업체들을 만족한 군과 불만족한 군으로 나누고 각각의 군집에 대해 시급하게 관리되어야 할 공급업체들과 이들을 관리하는데 우선시되는 중요 관리 요인들을 도출하여 여행사와 공급업체들 간의 협업 비즈니스 프로세스 개선 전략에 반영하였다. 이와 같은 결과는 본 연구에서 제안된 모델의 실무 적용 가능성을 보여주는 것으로 해석할 수 있다. Traditional approaches to manage collaborative business processes have focused on developing techniques of process management systems and evaluating suppliers in terms of resources and conceptual factors. While these studies have shown adequate strategies for managing suppliers and collaborative business processes, most of them overlooked the importance of identifying detailed process based on supplier’s satisfaction. Thus, this study proposes a framework that finds important processes through analyzing survey data based on supplier’s satisfaction and propose an identification of collaborative process in practical level. In this framework, the questions of survey are carefully designed based on factors for supplier’s satisfaction on previous literature. The survey data is analyzed with K-means clustering algorithm, decision tree and analytical hierarchy process to find detailed factors related with collaborative processes and to identify suppliers which have high priority of management. The application study was implemented on a travel agency in Korea. The suppliers of a travel agency were divided into two groups one is satisfied and the other is unsatisfied and the management-priority of suppliers in each groups and important factors represent detailed processes related with collaborative processes were conducted through analysis. The result of analysis was applied for strategies of collaborative process improvement between travel agency and its suppliers. The result showed the proposed framework can provide a basis of supplier management for improving collaborate business processes in aspect of suppliers satisfaction. KCI Citation Count: 1